Фінансово-економічна безпека комерційних банків України - Сак, Тетяна Василівна; Sak, T. V. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Проведено оцінку діяльності комерційних банків в Україні, визначено основні загрози з поділом їх на ризики внутрішнього та зовнішнього середовища. Розраховано інтегральний показник фінансово-економічної безпеки банків України. Обґрунтовано напрями забезпечення фінансово-економічної безпеки комерційних банків України.

The article provides the assessment of commercial banks activity in Ukraine according to the indicators characterizing the level of banks security and efficiency. The main threats of the banking sector are determined and classified as risks of internal and external environment. The integral indicator of financial and economic security of Ukrainian banks is calculated in terms of the main generalizing indicators according to their threshold values by applying the method of indicators standardization. The security status of commercial banks in Ukraine is identified. The author substantiates the ways to ensure the financial and economic security of commercial banks in Ukraine based on: achieving financial stability and financial independence of banks, more efficient use of capital. It is suggested that financial and economic security should be provided by eliminating threats at the national and international level as well as developing a single comprehensive concept of security and protection that will be aimed at raising the level of population confidence in banks and development of the national economy.
Financial and Economic Security of Commercial Banks in Ukraine
Keywords: фінансово-економічна безпека банку; загрози; ризики; порогове значення; інтегральний показник безпеки; financial and economic security of the bank; threats; risks; threshold value; integral security indicator